Glycyrrhetinic Acid and Its Derivatives: Anti-Cancer and Cancer Chemopreventive Properties, Mechanisms of Action and Structure- Cytotoxic Activity Relationship - Roohbakhsh, Ali; Iranshahy, Milad; Iranshahi, Mehrdad (Current Medicinal Chemistry, 2016)
The anti-cancer properties of liquorice have been attributed, at least in part, to glycyrrhizin (GL). However, GL is not directly absorbed through the gastrointestinal tract. It is hydrolyzed to 18-β-glycyrrhetinic acid (GA), the pharmacologically active metabolite, by human intestinal microflora. GA exhibits remarkable cytotoxic and anti-tumor properties. The pro-apoptotic targets and mechanisms of action of GA have been extensively studied over the past decade. In addition, GA is an inexpensive and available triterpene with functional groups (COOH and OH) in its structure, which make it an attractive lead compound for medicinal chemists to prepare a large number of analogues. To date, more than 400 cytotoxic derivatives have been prepared on the basis of GA scaffold, including 128 cytotoxic derivatives with IC50 values less than 30 μM. Researchers have also succeeded in synthesizing very potent cytotoxic derivatives with IC50s ≤ 1 μM. Studies have shown that the introduction of a double bound at the C1-C2 position combined with an electronegative functional group, such as CN, CF3 or iodine at C2 position, and the oxidation of the hydroxyl group of C3 to the carbonyl group, significantly increased cytotoxicity. This review describes the cytotoxic and anti-tumor properties of GA and its derivatives, targets and mechanisms of action and provides insight into the structure-activity relationship of GA derivatives.
Keywords: 18-α-glycyrrhetinic acid